Broom sorghum - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
One of the most important crops in the Santa Cruz region of Bolivia is broom sorghum. It is used for making brooms and has become a major local industry since the crop was introduced in the early 1950s. There are several varieties of sorghum that...